PET/CT Fusion Scan Prevents Futile Laparotomy in Early Stage Pancreatic Cancer. (November 2015) - Kim, Richard; Prithviraj, Gopi; Kothari, Nishi; Springett, Greg; Malafa, Mokenge; Hodul, Pamela; Kim, Jongphil; Yue, Binglin; Morse, Brian; Mahipal, Amit
<x xml:space="preserve">Abstract</x> Background Surgical resection with negative margins is the only curative approach for pancreatic cancer. A paucity of data exists in using PET/CT scan as staging workup in resectable pancreatic cancer. The aim of this study is to determine if PET/CT prevents futile laparotomy by detecting occult metastatic disease in patients with resectable or borderline resectable pancreatic cancer. Methods Patients were included using institutional PET/CT data base incorporating National Oncologic PET Registry with diagnosis of resectable or borderline resectable pancreatic cancer from 2005 to 2012. Clinical, radiographic, and pathologic characteristics were evaluated. The impact of PET/CT on patient management was estimated by calculating the percentage of patients whose treatment plan was altered secondary to PET/CT. Results We identified 285 patients with early stage pancreatic cancer who received PET/CT as part of initial staging workup. Upon initial workup (CT + EUS), 62% of patients were considered resectable, and 38% were borderline resectable. Addition of PET/CT scan changed the management in 10.9% (n = 31) of the patients (95% CI, 8%–15%). Metastatic lesions were confirmed with biopsy in 19 patients (61%). The proportion of change in treatment plan was significantly higher in patients who were initially considered to have borderline resectable compared with resectable malignancy (17% vs 7%, P = 0.019). In 199 patients who underwent surgery, 18.1% (n = 36) were found to have metastatic disease intraoperatively. Conclusions PET/CT helped improve detection of occult metastases, ultimately sparing these patients a potentially unnecessary surgery. The role of PET/CT scan should be validated in prospective study.